EFEKTIFITAS PEMANFAATAN MEDIA AUDIO PEMBELAJARAN DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS 1 SUBTEMA TUBUHKU DI SDN MIMBAAN 2 SITUBONDO - Vidya Pratiwi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2017)
Improving the quality of learning is one of the most fundamental things to improve the quality of education as a whole. But the lack of creativity of teachers as teachers in presenting a learning media that is more fun and close to the world of students cause lesson material presented by the teacher is not running optimally. As a result students feel bored, less interesting lessons, even full of mystery, resulting in less satisfactory learning outcomes. Problem formulation How is the effectiveness of the use of learning audio media in improving student learning outcomes in the subjects of Bahasa Indonesia Sub Theme Body ?. Research Objectives To obtain an overview of the effectiveness of the use of audio media learning in improving student learning outcomes in the subjects of Bahasa Indonesia Sub Theme Body. This research is PTK (Research Action Class). Classroom Action Research is done because of the problems faced by educators in the process of learning in the classroom. The implementation of TOD will be carried out at SD Mimbaan 2 Situbondo with 6 weeks implementation time in September 2017 - November 2017. The subject of this research is all students of class 1 consisting of 1 class of 26 students at SD Mimbaan 2 Situbondo.The PTK procedure is cyclical. One cycle consists of four phases, namely: planning phase, implementation phase, observation phase, reflection phase. Data presentation technique used in this research is descriptive analysis that is an analysis without using statistic test. it is known that the number of students who completed 13 people with 57.69% percentage and categorized less well. The learning outcomes of a class is said to be complete if there are ≥ 75% of students who have achieved a score of ≥ 70 from a maximum score of 100. Therefore the result of classical student learning in cycle 1 is still not complete. But the completeness of student learning outcomes in cycle 1 has increased and better than previous or prasiklus. In cycle 2 it is known that the number of complete students is 17 people. The completeness of the desired Indonesian learning result in SDN 2 Mimbaan is 75%. Learning outcomes in cycle 2 shows that the completeness of student learning outcomes has increased and better than the 1st cycle of 80.76% with good category. Classically student learning outcomes in cycle 2 is declared complete. Increase percentage of learning result completeness from cycle 1 to cycle 2 is 23,07%